Canned citrus processing : techniques, equipment, and food safety - Shan, Yang (Academic Press, 2015)
Citrus is one of the most popular fruits around the world, and can be successfully cultivated in more than 140 countries. Producing 75% of citrus consumed in the global market, China has become the new "Kingdom of Canned Citrus. Canned Citrus Processing: Techniques, Equipment, and Food Safety comprehensively presents the technical and development trends of the canned citrus industry. This book provides solutions to typical problems of canned citrus manufacturing and processing; presents an overview of the canned citrus industry, introduces canned citrus processing machinery and equipment, and discusses the processing quality, safety control, and related standards.